THREE-PHASE FUZZY MODEL OF A DYNAMIC PRODUCTION SYSTEM - Usenik, Janez; Vidiček, Meta (Journal of Energy Technology, 2024)
In this article, a three-phase fuzzy model of controlling a dynamic production system is presented. A power supply system can be an example of such a system. Fuzzy system control follows a stochastic mathematical closed-loop model of the control of stocks (additional capacities) in a production system. The fuzzy model is demonstrated with a numerical example.
Keywords: dynamic production system; control; fuzzy model; fuzzy reasoning